2005
DOI: 10.1111/j.1469-8137.2005.01536.x
|View full text |Cite
|
Sign up to set email alerts
|

The uptake, metabolism, transport and transfer of nitrogen in an arbuscular mycorrhizal symbiosis

Abstract: Summary Nitrogen (N) is known to be transferred from fungus to plant in the arbuscular mycorrhizal (AM) symbiosis, yet its metabolism, storage and transport are poorly understood. In vitro mycorrhizas of Glomus intraradices and Ri T‐DNA‐transformed carrot roots were grown in two‐compartment Petri dishes. 15N‐ and/or 13C‐labeled substrates were supplied to either the fungal compartment or to separate dishes containing uncolonized roots. The levels and labeling of free amino acids (AAs) in the extraradical my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
171
1
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(194 citation statements)
references
References 48 publications
8
171
1
8
Order By: Relevance
“…AM fungi have access to inorganic or organic forms of N (Lopez-Pedrosa et al, 2006;Cappellazzo et al, 2008) and translocate them via Arg from the extra-to the intraradical mycelium, where N is transferred to the plant in inorganic form (Govindarajulu et al, 2005;Jin et al, 2005). However, the molecular form in which N is transferred from AM fungi to their hosts is still under debate: while Govindarajulu et al (2005) considered NH 4 + , Chalot et al (2006) added NH 3 as a potential candidate.…”
Section: Discussionmentioning
confidence: 99%
“…AM fungi have access to inorganic or organic forms of N (Lopez-Pedrosa et al, 2006;Cappellazzo et al, 2008) and translocate them via Arg from the extra-to the intraradical mycelium, where N is transferred to the plant in inorganic form (Govindarajulu et al, 2005;Jin et al, 2005). However, the molecular form in which N is transferred from AM fungi to their hosts is still under debate: while Govindarajulu et al (2005) considered NH 4 + , Chalot et al (2006) added NH 3 as a potential candidate.…”
Section: Discussionmentioning
confidence: 99%
“…N uptake and incorporation into amino acids via the glutamine synthetase/glutamate synthase (GS/GOGAT) cycle has been found in AM fungi (Smith et al, 1985). Stable isotope labeling has now suggested that inorganic nitrogen is taken up by the extraradical mycelium, incorporated into amino acids, translocated from extra-to intraradical fungal structures as arginine and then transported as ammonium to the plant (Govindarajulu et al, 2005;Jin et al, 2005). Further support for this uptake route comes from the finding that transcript abundance of key enzymes of nitrogen assimilation and arginine breakdown preferentially accumulate in extra-and intraradical mycelia, respectively (Govindarajulu et al, 2005).…”
Section: Nitrogen Transfer At the Mycorrhizal Interfacementioning
confidence: 99%
“…Various models have been proposed by Jin et al (2005), Govindarajulu et al (2005) and Chalot et al (2006) which involve a number of steps for direct transfer of ammonia from fungal to plant cells (i) AM fungi take up inorganic N (NH + 4 , NO − 3 ); (ii) absorbed N is mostly incorporated and stored in arginine; (iii) AM fungi assimilate the N through GS/GOGAT, asparagine synthase and the urea cycle; (iv) stored arginine can be co-transported with PolyP intact to the intraradical mycelium form the extraradical mycelium of AM fungi, and arginine is also bi-directionally transported within the extraradical mycelium; and (v) N released from transported arginine is transferred to the host as NH + 4 and can be incorporated into other free amino acids in mycorrhizal roots, while carbon (C) not transferred to the host is recycled back to the extraradical mycelium. In analogy to the path of symbiotic P i uptake, the arbuscule may be the site of symbiotic nitrogen uptake involving plant encoded nitrogen transporters located within the periarbuscular plant membrane (Paszkowski, 2006).…”
Section: Nitrogen Transfer At the Mycorrhizal Interfacementioning
confidence: 99%
“…To follow the uptake, assimilation and transfer of nitrogen in the arbuscular mycorrhizal symbiosis, we added isotopically labeled substrates to in vitro arbuscular mycorrhizal cultures of carrot (Daucus carota L.) roots colonized by G. intraradices. [28][29][30] When grown in divided Petri plates, this model mycorrhiza excludes other microorganisms and prevents diffusion of nonvolatile solutes between the compartments. This model system shows normal life cycle and development of fungal morphology.…”
Section: Introductionmentioning
confidence: 99%